Glass for liquid flash capillary array as well as preparation method and application of glass

The glass materials prepared by specific composition and process have solved the problem of difficult to prepare glass with low refractive index, crystallization resistance, suitable softening point, pressure resistance and radiation resistance in the prior art, and realized the use of liquids Preparation of high-performance glass materials for flash capillary array detectors.

CN119504142AActive Publication Date: 2025-02-25CHINA BUILDING MATERIALS ACADEMY CO LTD

Patent Information

Application Number
CN202411616615.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-25
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

The prior art is difficult to prepare a glass material with low refractive index, crystallization resistance, suitable softening point, pressure resistance and radiation resistance for liquid flash capillary array detectors, especially at high temperatures and stability. High roundness requirements.

Method used

A glass material with a specific composition is used, including 80-85% SiO2, 0.5-4% Al2O3, 4.5-8% B2O3, 2-8% K2O and Na2O, 1-2% PbO and CdO, 1.5-4% ZrO2, 1-1- 4% KFH2 and K2SiF6, 0.2-0.5% BaF2 and 0.5-1% CeO2 were prepared by fine raw material mixing, melting and annealing processes.

Benefits of technology

The prepared glass material has a refractive index between 1.465 and 1.480, a softening temperature between 650 and 700°C, a compressive strength of ≥1500MPa, and has no crystallization at 750 and 1100°C. It has excellent radiation resistance and is suitable for liquid flash Preparation of capillary array detectors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119504142A_ABST
    Figure CN119504142A_ABST
Patent Text Reader

Abstract

The invention relates to glass for a liquid flash capillary array as well as a preparation method and application of the glass. The glass comprises the following components by mole percent: 80-85% of SiO2; 0.5% to 4% of Al2O3; 4.5 to 8% of B2O3; the sum of the contents of K2O and Na2O is 2-8%; the sum of the PbO content and the CdO content is 1-2%; 1.5%-4% of ZrO2; the sum of the contents of the KFH2 and the K2SiF6 is 1 to 4 percent; 0.2% to 0.5% of BaF2; and 0.5%-1% of CeO2. The technical problem to be solved is how to provide glass with low refractive index, high softening point, good devitrification resistance, good pressure resistance and radiation resistance, so that the glass can be used for preparing the liquid flash capillary tube array.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fast neutron imaging detection, and in particular relates to glass for liquid scintillator capillary array and a preparation method and application thereof. Background Art

[0002] In the field of nuclear detection, image diagnosis technology based on the principle of fast neutron imaging is widely used to obtain information such as the radiation intensity distribution in the source area and the dynamic surface density distribution, and to study the characteristics of physical processes under extreme conditions. The selection of scintillation fiber array materials in fast neutron imaging detectors is the key to achieving high-resolution fast neutron imaging.

[0003] Liquid scintillator micropore capillary array detectors are the focus of research because they are most likely to achieve micron-level resolution for fusion neutrons. High numerical aperture is an important guarantee for liquid scintillator capillary arrays to achieve high detection efficiency, which depends on the refractive index of the capillary glass material and the liquid scintillator. According to application requirements, the numerical aperture of the liquid scintillator capillary array needs to be greater than 0.50. According to the following numerical aperture calculation formula:

[0004]

[0005] Where NA is the numerical aperture, n core is the refractive index of the liquid scintillator, n cladding is the refractive index of the capillary glass. When the EJ-309 liquid scintillator (refractive index 1.57) currently used internationally is used as the filler, the refractive index of the capillary glass should be less than 1.48.

[0006] However, the glass material prepared by the prior art, quartz glass has a refractive index of 1.46, but due to its too high softening point, it is impossible to add the outer wall absorption layer material, and the problem of optical crosstalk between capillaries cannot be solved; phosphate glass has a low refractive index, and the refractive index can be reduced to below 1.4, but the fiber-forming performance is poor, it is easy to crystallize at high temperature, and it cannot be used to draw capillaries. Therefore, this field is in urgent need of glass materials that meet the refractive index requirements of liquid scintillator capillary arrays and have anti-crystallization properties at high temperatures. In addition, the capillary glass material used for liquid scintillator capillary arrays should also have a suitable softening point to avoid the extrusion deformation caused by the low softening point during the hot melt pressing process, which leads to a reduction in the roundness of the micropore array. Moreover, in order to ensure that the liquid scintillator microporous capillary array has a high detection efficiency, a glass tube with an opening area ratio of ≥70% must be used. Such a large opening ratio requires the use of thin-walled glass tubes, which requires that the glass material must have a high compressive strength to prevent it from being damaged due to wall thinning during the fiber drawing process; at the same time, the glass material should also be resistant to neutron radiation to ensure its service life during fast neutron imaging detection.

[0007] How to prepare glass that meets the requirements of liquid scintillator micropore capillary array detectors and has the above-mentioned multiple properties so that it can be better used in liquid scintillator capillary array detectors is a research hotspot in the field of fast neutron imaging detectors. Summary of the invention

[0008] The main purpose of the present invention is to provide a glass for liquid scintillator capillary array and its preparation method and application. The technical problem to be solved by the present invention is how to provide a glass for liquid scintillator capillary array, which has a low refractive index, excellent anti-crystallization performance, suitable softening point, good pressure resistance and strong radiation resistance, and can be used as a skeleton material for liquid scintillator capillary array, for preparing liquid scintillator micropore array detector, and further applied to fast neutron imaging detection.

[0009] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions. According to the glass for preparing a liquid scintillation capillary array proposed by the present invention, the glass components, in terms of molar percentage, include:

[0010] 80-85% SiO2; 0.5-4% Al2O3; 4.5-8% B2O3; the sum of K2O and Na2O is 2-8%; the sum of PbO and CdO is 1-2%; 1.5-4% ZrO2; the sum of KFH2 and K2SiF6 is 1-4%; 0.2-0.5% BaF2; 0.5-1% CeO2.

[0011] Preferably, in the aforementioned glass, the sum of the contents of K2O and Na2O is 2-5%.

[0012] Preferably, in the aforementioned glass, the ZrO2 is 2-4%.

[0013] Preferably, in the aforementioned glass, the sum of the contents of KFH2 and K2SiF6 is 1.5-4%.

[0014] Preferably, the aforementioned glass satisfies the following conditions:

[0015] a. The molar percentage of SiO2 is X1, the total molar percentage of KHF2 and K2SiF6 is X2, and X1: X2 is 20 to 75: 1;

[0016] b. The total molar percentage of SiO2, K2O and Na2O is X3, and the total molar percentage of B2O3 and Al2O3 is X4; X3:X4 is 9-14:1;

[0017] c. The total molar percentage of SiO2 and Al2O3 is X5, the total molar percentage of PbO and CdO is X6, and X5:X6 is 40 to 90:1.

[0018] Preferably, the aforementioned glass satisfies one or more of the following conditions: a. the ratio of X1:X2 is 20 to 60:1; b. the ratio of X3:X4 is 10 to 14:1; c. the ratio of X5:X6 is 50 to 90:1.

[0019] Preferably, the aforementioned glass, wherein the glass refractive index n d 1.465~1.480; no crystallization at 750~1100℃; softening temperature T f 650~700℃; the compressive strength of the glass is ≥1500Mpa; when the glass is 10mm thick, use 252 When Cf is used as a fast neutron radiation source, after being irradiated with a total dose of 100 Gy of fast neutrons, the transmittance at 560 nm decreases by ≤1.3%.

[0020] The purpose of the present invention and the technical problem solved by the present invention are also achieved by adopting the following technical solutions. According to a method for preparing glass for preparing a liquid scintillation capillary array proposed by the present invention, the method comprises the following steps:

[0021] S1: The raw materials are uniformly mixed to prepare a batch material; in terms of molar percentage, the batch material includes 80-85% SiO2; 0.5-4% Al2O3; 4.5-8% B2O3; the sum of K2O and Na2O is 2-8%; the sum of PbO and CdO is 1-2%; 1.5-4% ZrO2; the sum of KFH2 and K2SiF6 is 1-4%; 0.2-0.5% BaF2; and 0.5-1% CeO2;

[0022] S2: Melting, clarifying and homogenizing the batch material prepared in S1 to obtain glass liquid;

[0023] S3: After cooling the glass liquid obtained in S2 to 1200-1300°C, it is molded and precision annealed in sequence.

[0024] Preferably, in the aforementioned preparation method, the S2 melting temperature is 1500-1600°C and the time is 10-15h.

[0025] Preferably, the aforementioned preparation method further comprises the following steps: before the batch material is melted, a melting device for melting the batch material is preheated to a temperature of 1300-1400°C.

[0026] Preferably, in the aforementioned preparation method, the precision annealing comprises: the precision annealing comprises: heating to 550-650°C at 1.5-2.5°C / min, keeping the temperature for 5-8h, and then cooling to room temperature at 1.0-2.0°C / h.

[0027] The purpose of the present invention and the solution of its technical problems are also achieved by the following technical solutions. According to a liquid scintillator micropore array detector proposed by the present invention, the glass capillaries in the micropore array area are made of the glass described in the above technical solution; and the liquid scintillator is filled in each microcapillary of the capillary array.

[0028] By means of the above technical solution, the glass for liquid scintillation capillary array and its preparation method and application proposed by the present invention have at least the following advantages:

[0029] 1. The glass for liquid scintillator capillary array provided by the present invention has a refractive index n d is 1.465-1.480, which ensures that the prepared liquid scintillation capillary array has a higher fiber optical numerical aperture and further ensures that the liquid scintillation capillary array has a higher detection efficiency; the softening temperature T f The temperature of the liquid scintillator capillary array is 650-700℃; it ensures that the liquid scintillator capillary array is only compressed by the sheathing glass during the hot melting and pressing process, and the deformation of the liquid scintillator capillary array is extremely small, ensuring its roundness, and further ensuring the detection efficiency of the liquid scintillator capillary array, while the softening point is not too high, avoiding the problem of being unable to add light absorbing materials; there is no crystallization and phase separation at 750-1100℃, it has good anti-crystallization performance and glass stability, and the compressive strength is ≥1500MPa, which can meet the special manufacturing process requirements of the liquid scintillator capillary array; it also has excellent radiation resistance. Therefore, the glass material provided by the present invention can be used to prepare liquid scintillator capillary arrays, and is further used in fast neutron imaging detectors, and has a broad prospect of promotion and application in the field of neutron detection.

[0030] 2. The method for preparing glass for liquid scintillator capillary array provided by the present invention limits glass components and adjusts process steps and process parameters so that the prepared glass material meets the preset glass performance requirements.

[0031] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The figure shows the comparison of the transmittance (at 560 nm) of the glass material prepared in Example 1 of the present invention before and after being irradiated with a total dose of 100 Gy fast neutrons. DETAILED DESCRIPTION

[0033] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined purpose of the invention, the following, in combination with the accompanying drawings and preferred embodiments, describes in detail a glass for liquid scintillator capillary array and its preparation method and application of its specific implementation method, structure, characteristics and effects.

[0034] The following is an explanation of the range of each component (ingredient) of the glass material of the present invention. In the present invention, unless otherwise specified, the content and total content of each component are all expressed in molar percentage, that is, the content and total content of each component are expressed as the molar percentage of the total amount of glass material converted into the composition of oxides or fluorides. Here, the "composition converted into oxides or fluorides" means that when the oxides, fluorides, composite salts and hydroxides used as raw materials for the glass material components of the present invention decompose and transform into oxides or fluorides when melted, the total amount of the oxides or fluorides is taken as 100%.

[0035] The glass used for the liquid scintillator microhole array of the present invention comprises, in terms of molar percentage, the following glass components:

[0036] 80-85% SiO2; 0.5-4% Al2O3; 4.5-8% B2O3; the sum of K2O and Na2O content is 2-8%; the sum of PbO and CdO content is 1-2%, 1.5-4% ZrO2, the sum of KFH2 and K2SiF6 content is 1-4%, 0.2-0.5% BaF2, 0.5-1% CeO2.

[0037] The SiO2 is a glass-forming oxide and an important component of the basic skeleton structure of glass. The present invention strictly limits the content of SiO2 in the glass to 80-85%, which not only helps to provide the structural stability and chemical durability of the glass, but also helps to maintain the radiation resistance of the glass. Too high a SiO2 content will increase the melting point of the glass, resulting in difficulty in the glass melting process, and the glass will be difficult to cooperate with the light-absorbing filament to be drawn into a fiber filament; too low a SiO2 content will lead to a decrease in the stability of the glass skeleton network structure, thereby reducing the structural stability and chemical durability of the glass, and may even make the glass more susceptible to chemical corrosion and environmental factors.

[0038] Al2O3 is a glass structure regulating oxide, and its content in glass will affect the softening temperature and melting temperature of glass. Based on this, the present invention limits its content in glass to 0.5-4%. If its content in glass is higher than 4%, the melting temperature of glass will increase significantly, making glass melting difficult; a high content of Al2O3 in glass will also lead to enhanced bonding of glass network, thereby significantly increasing the softening temperature of glass, making it difficult to add wall outer absorption layer material to the glass material, and the problem of light crosstalk between capillaries will be difficult to avoid; and if its content in glass is lower than 0.5%, the chemical stability and thermal stability of glass will be reduced; and the softening temperature of glass will be difficult to meet the design requirements.

[0039] B2O3 is a glass-forming oxide and the main component of the glass skeleton. It is also a solvent that reduces the viscosity of the glass. Its structural components include boron oxide triangle [BO3] and boron oxide tetrahedron [BO4]. When B2O3 is melted at high temperature, it is generally difficult to form boron oxide tetrahedron, but when it is melted at low temperature, under certain conditions, B 3+ There is a tendency to capture free oxygen to form tetrahedrons, which not only helps to improve the compactness of the glass structure, but also helps to improve the low-temperature viscosity of the glass. However, since B2O3 has the characteristics of reducing the viscosity of the glass at high temperatures and increasing the viscosity of the glass at low temperatures, and is also the main component that reduces the refractive index of the glass, the content range of B2O3 in the glass is relatively small. The present invention limits its content in the glass to 4.5-8%. When the content of B2O3 in the glass is lower than 4.5%, the fluxing effect is not good, and the chemical stability of the glass will also be reduced; when the content of B2O3 in the glass is greater than 8%, the anti-crystallization ability of the glass will be significantly deteriorated. Preferably, the content of B2O3 in the glass is 4.5-7.5%, and the glass prepared under this condition has better anti-crystallization performance.

[0040] Na2O and K2O are network outer oxides of glass. Alkali metal ions can easily move and diffuse in the glass, which can reduce the viscosity of glass during high-temperature melting and make the glass easy to melt. They are good fluxing agents. However, too much Na2O and K2O will cause the refractive index of the glass to decrease, making it impossible to ensure that the numerical aperture requirements of the liquid scintillator capillary can be met. Therefore, the present invention limits the sum of the contents of the two to 2-8%, and one or more of them can be introduced according to appropriate adjustments based on the thermal properties of the glass material of the matching absorption filament. Preferably, the sum of the contents of Na2O and K2O is limited to 2-5%, within which the refractive index of the prepared glass can better meet the preset requirements.

[0041] Lead and cadmium are both heavy metal elements with high atomic numbers and high mass attenuation coefficients, so PbO and CdO are widely used in the field of radiation shielding. In the glass composition of the present invention, the addition of PbO and CdO can improve the radiation resistance of the glass, but too much PbO and CdO may reduce the thermal stability of the glass, and there are also environmental and health risks. The glass material of the present invention contains at least one of PbO and CdO, and the sum of the contents of PbO and CdO in the glass is strictly limited to 1-2%. This content of PbO and CdO helps to balance the stability and radiation resistance of the glass material.

[0042] The content of ZrO2 is 1.5-4%; in the glass material of the present invention, ZrO2 can increase the transition temperature and softening temperature of the glass, and enhance the chemical stability and mechanical strength of the glass. The present invention limits its content to 1.5-4% to increase the softening temperature and compressive strength of the glass material. However, adding too much ZrO2 will increase the phase separation tendency of the glass; adding too little may not achieve the design purpose of the present invention. Preferably, the ZrO2 is 2-4%; strictly limiting its minimum dosage can better ensure that the softening temperature and compressive strength of the glass material meet the preset requirements.

[0043] KFH2 and K2SiF6 are both potassium fluoride composite salts, which are used to reduce the refractive index of the glass of the present invention. They also have the function of reducing the viscosity of the glass during high-temperature melting, thus playing a fluxing effect. The present invention limits the total content of KFH2 and K2SiF6 to 1-4%, so as to avoid excessive addition of KFH2 and K2SiF6 to the glass, which may increase the phase separation tendency of the glass. Preferably, the present invention limits the total content of KFH2 and K2SiF6 to 1.5-4%, so as to better control the phase separation problem of the glass while ensuring that the refractive index of the glass meets the preset requirements.

[0044] BaF2 is barium fluoride. Adding a small amount can significantly reduce the refractive index of glass. However, since a single fluoride can easily destroy the glass structure and cause glass phase separation, the content range of BaF2 allowed to be added to the glass is relatively small. Preferably, a maximum of 0.5% BaF2 is allowed to be added to the glass material of the present invention.

[0045] In the glass material of the present invention, CeO2 has two functions: on the one hand, it acts as a stabilizer, and on the other hand, CeO2 exists in the glass structure. 3+ With Ce 4+ The electricity price balance of mutual conversion, where Ce 3+ It tends to capture holes and be oxidized to form Ce 3+(+) , Ce 4 + It has a tendency to capture free electrons and be reduced to form Ce4 4+(-), so that the free electrons generated by irradiation cannot enter the defects in the glass structure, thereby preventing the formation of color centers and avoiding glass coloring; on the other hand, CeO2 also serves as a glass melting clarifier. Therefore, CeO2 is indispensable in the glass system. The present invention limits its content to 0.5-1%. Too much CeO2 will cause the color of the glass to change, thereby affecting its transparency, and may also increase the tendency of glass crystallization.

[0046] The glass prepared by the above scheme has low refractive index, high softening point and anti-crystallization ability, strong pressure resistance and good radiation resistance. It can be used as the skeleton material of liquid scintillator capillary array, used to prepare liquid scintillator microcapillary array detectors, and further used in fast neutron imaging detection.

[0047] Preferably, the above technical solution meets the following conditions:

[0048] In some embodiments, the molar percentage of SiO2 in the glass components is X1, the total molar percentage of KHF2 and K2SiF6 is X2, and X1:X2 is 20-75:1; this can ensure that the glass has a high anti-crystallization performance and better inhibit the phase separation tendency of the glass. Further preferably, X1:X2) is 20-60:1, which can make the glass have better anti-crystallization performance and better inhibit the phase separation tendency of the glass.

[0049] In some embodiments, the total molar percentage of SiO2, K2O and Na2O in the glass components is X3, the total molar percentage of B2O3 and Al2O3 is X4; X3:X4 is 9-14:1; further preferably, X4; X3:X4 is 10-14:1. Strictly limiting the ratio of the aforementioned components is beneficial to improving the anti-crystallization performance of the glass and maintaining the softening temperature of the glass within a specific range.

[0050] In some embodiments, the total molar percentage of SiO2 and Al2O3 in the glass components is X5, preferably, the total molar percentage of PbO and CdO is X6, and X5:X6 is 40-90:1; further preferably, X5:X6 is 50-90:1; strictly limiting the ratio of the aforementioned components helps to better balance the transmittance of the glass, and helps to balance the chemical stability, thermal stability, optical transmittance, and radiation resistance of the glass.

[0051] The glass material provided by the present invention has a refractive index n d is 1.465~1.480; it ensures that the prepared liquid scintillation capillary array has a higher fiber optical numerical aperture, and further ensures that the liquid scintillation capillary array has a higher detection efficiency. Glass softening temperature T fBetween 650 and 700°C, it is ensured that the liquid scintillator capillary array is only compressed and formed by the sheathing glass during the hot melt pressing process. Compared with the traditional preparation method of liquid scintillator capillary array, the process steps are simplified, the deformation of the liquid scintillator capillary array is extremely small, its roundness is ensured, and the detection efficiency of the liquid scintillator capillary array is further ensured; at the same time, the softening point is not too high to avoid the problem of being unable to add light absorbing materials. The glass provided by the present invention has good anti-crystallization performance at 750-1100°C; it has good anti-crystallization performance and glass stability, can meet the special manufacturing process requirements of liquid scintillator capillary arrays, and can achieve that the glass itself still maintains its own characteristics unchanged after multiple high-temperature drawing and high-temperature melting and pressing; and the compressive strength of the glass material is ≥1500MPa, which ensures the stability of the glass material during the drawing process; when the glass material is 10mm thick, use 252 Cf is used as a fast neutron radiation source. After being irradiated with a total dose of 100Gy of fast neutrons, the transmittance at 560nm after being irradiated with a total dose of 100Gy of fast neutrons decreases by ≤1.3%, which has excellent radiation resistance. Therefore, the glass material provided by the present invention can be used as a skeleton material for a liquid scintillator capillary array, used to prepare a liquid scintillator micropore array detector, and further used in fast neutron imaging detection.

[0052] The present invention also provides a method for preparing liquid scintillation capillary array glass, which comprises the following steps:

[0053] Preparation of S1 batch material: weigh the raw materials and mix them evenly. According to molar percentage, the batch material includes 80-85% SiO2; 0.5-4% Al2O3; 4.5-8% B2O3; the sum of K2O and Na2O content is 2-8%; the sum of PbO and CdO content is 1-2%, 1.5-4% ZrO2, the sum of KFH2 and K2SiF6 content is 1-4%, 0.2-0.5% BaF2, and 0.5-1% CeO2.

[0054] S2 Melting, Clarifying and Homogenizing: The present invention first heats the furnace to 1300-1400°C before adding the batch materials. This is because only when the furnace is preset to the above temperature can certain chemical reactions in the batch materials be carried out. If the furnace is not preheated or the preheating temperature is not reached, the batch materials are loose and have poor heat conduction capabilities, making it difficult to melt them fully to form a homogenized glass liquid. When the preheating temperature of the furnace is too low, most of the heating heat will be used to increase the temperature of the raw materials themselves to the reaction temperature, and the heat cannot be directly used to melt the batch materials, thereby reducing the efficiency of the entire melting process.

[0055] When the furnace reaches the preset temperature, the batch material prepared by S1 is gradually added to the crucible in the furnace in multiple times, and the temperature is raised to 1500-1600°C for high-temperature melting, and the melting time is 10-15 hours; and the melting process is continuously stirred, clarified and homogenized. The present invention strictly limits the melting temperature and melting time to ensure that the glass solution can be completely melted in the shortest time, improve efficiency and save resources. The crucible and stirring rod need to have corrosion resistance to avoid being corroded by the glass liquid and affecting the performance of the glass. In some embodiments, a pure platinum (Pt) crucible is used.

[0056] S3 forming and annealing: the glass liquid obtained by S2 is cooled to 1200-1300°C, and then mechanical forming is performed; after mechanical forming is completed, precision annealing is performed. During the precision annealing process, the temperature is increased from room temperature to 550-650°C at a heating rate of 1.5-2.5°C / min, and kept at a temperature of 5-8h, and then cooled to room temperature at a rate of 1.0-2.0°C / h. In some embodiments, the room temperature is 25±1°C. The present invention strictly limits the precision annealing process conditions, which is conducive to better eliminating stress in the glass and improving the mechanical strength of the glass.

[0057] The present invention also provides a liquid scintillator micropore array detector, wherein the glass capillaries in the micropore array region are made of glass prepared by the aforementioned technical solution; and the liquid scintillator is filled in each microcapillary of the capillary array.

[0058] The present invention also provides a method for preparing a liquid scintillation capillary array, which comprises the following steps:

[0059] The glass material prepared by the above scheme is made into a glass capillary, and then a surrounding tube is surrounded by an absorption wire outside the capillary glass tube, and then drawn into single-filament and multi-filament, the multi-filament is regularly arranged in a sheath glass of matching shape, and then hot-melt pressed into a blank plate section, and then through mechanical processing, cleaning, liquid scintillator filling, adhesive packaging and other steps to obtain a liquid scintillator microporous array.

[0060] The present invention will be further described below in conjunction with specific embodiments, but this should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.

[0061] Unless otherwise specified, the materials, reagents, etc. involved below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods well known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the common meanings understood by ordinary technicians in the field to which the present invention belongs.

[0062] The testing methods of various performance indicators in the embodiments and comparative examples of the present invention are as follows:

[0063] Glass refractive index n d Test: Tested according to GB / T 7962.1-2010 colorless optical glass test method;

[0064] Softening temperature of glass T f Test: Tested according to GB / T 7962.16-2010 colorless optical glass test method;

[0065] Glass compressive strength test: Tested in accordance with GB / T 43874-2024 Glass material and product compression performance test method;

[0066] Anti-crystallization test of glass: observe and test the crystallization and phase separation at 750-1100℃;

[0067] Neutron irradiation resistance test of glass: When the glass material is 10mm thick, use 252 Cf was used as a fast neutron radiation source, and the changes in the transmittance of the test glass material were observed after irradiation with a total fast neutron dose of 100Gy.

[0068] Example 1

[0069] This embodiment provides a glass for a liquid scintillation capillary array and a preparation method and application thereof, comprising the following steps:

[0070] S1: The raw materials are mixed uniformly to prepare a batch material; in terms of molar percentage, the batch material includes 82% SiO2; 2.2% Al2O3; 5% B2O3; the sum of K2O and Na2O content is 5%; the sum of PbO and CdO content is 1.5%, 2% ZrO2; the sum of KFH2 and K2SiF6 content is 1.5%, 0.3% BaF2, 0.5% CeO2; the specific components are shown in Table 1.

[0071] S2: After preheating the furnace to 1350°C, gradually add the batch materials prepared in S1 into the platinum crucible in the furnace, raise the temperature to 1550°C for high-temperature melting, and the melting time is 12 hours; during the melting process, stir continuously, clarify and homogenize.

[0072] S3: Cooling the glass liquid obtained in S2 to 1250°C and then performing mechanical forming; after the mechanical forming is completed, precision annealing is performed, and the precision annealing includes: heating to 580°C at a heating rate of 2.0°C / min and keeping the temperature for 6 hours, and then cooling to room temperature at a heating rate of 1.5°C / h.

[0073] The refractive index n of the glass material prepared above is d Test: Softening temperature T f Test; compressive strength test; anti-crystallization test; neutron irradiation resistance test; the test methods are as described above.

[0074] Preparation of liquid scintillator capillary array: a capillary glass tube is prepared by using the glass material prepared in this embodiment, and then a surrounding tube is surrounded by an absorption wire outside the capillary glass tube, and after being drawn into single-filament and multi-filament, the multi-filament is regularly arranged in a shape-matching sheath glass, and then hot-melt pressed into a blank plate section, and then mechanical processing, cleaning, liquid scintillator filling, adhesive packaging and other steps are performed to obtain a liquid scintillator microporous array.

[0075] Example 2

[0076] The difference between this embodiment and embodiment 1 is that the distribution ratio of each group in the raw materials of this embodiment is as shown in Table 1, the remaining steps and parameters are the same as those of embodiment 1, and the detection indicators and methods are the same as those of embodiment 1.

[0077] Example 3

[0078] The difference between this embodiment and embodiment 1 is that the distribution ratio of each group in the raw materials of this embodiment is as shown in Table 1, the remaining steps and parameters are the same as those of embodiment 1, and the detection indicators and methods are the same as those of embodiment 1.

[0079] Example 4

[0080] The difference between this embodiment and embodiment 1 is that the distribution ratio of each group in the raw materials of this embodiment is as shown in Table 1, the remaining steps and parameters are the same as those of embodiment 1, and the detection indicators and methods are the same as those of embodiment 1.

[0081] Example 5

[0082] The difference between this embodiment and embodiment 1 is that the distribution ratio of each group in the raw materials of this embodiment is as shown in Table 1, the remaining steps and parameters are the same as those of embodiment 1, and the detection indicators and methods are the same as those of embodiment 1.

[0083] Example 6

[0084] The difference between this embodiment and embodiment 1 is that the distribution ratio of each group in the raw materials of this embodiment is as shown in Table 1, the remaining steps and parameters are the same as those of embodiment 1, and the detection indicators and methods are the same as those of embodiment 1.

[0085] Example 7

[0086] The difference between this embodiment and embodiment 1 is that the distribution ratio of each group in the raw materials of this embodiment is as shown in Table 1, the remaining steps and parameters are the same as those of embodiment 1, and the detection indicators and methods are the same as those of embodiment 1.

[0087] Example 8

[0088] The difference between this embodiment and embodiment 1 is that the distribution ratio of each group in the raw materials of this embodiment is as shown in Table 1, the remaining steps and parameters are the same as those of embodiment 1, and the detection indicators and methods are the same as those of embodiment 1.

[0089] Example 9

[0090] The difference between this embodiment and embodiment 1 is that the distribution ratio of each group in the raw materials of this embodiment is as shown in Table 1, the remaining steps and parameters are the same as those of embodiment 1, and the detection indicators and methods are the same as those of embodiment 1.

[0091] Example 10

[0092] The difference between this embodiment and embodiment 1 is that the distribution ratio of each group in the raw materials of this embodiment is as shown in Table 1, the remaining steps and parameters are the same as those of embodiment 1, and the detection indicators and methods are the same as those of embodiment 1.

[0093] Embodiment 11

[0094] The difference between this embodiment and embodiment 1 is that the distribution ratio of each group in the raw materials of this embodiment is as shown in Table 1, the remaining steps and parameters are the same as those of embodiment 1, and the detection indicators and methods are the same as those of embodiment 1.

[0095] Example 12

[0096] The difference between this embodiment and embodiment 1 is that the process parameters of this embodiment are as shown in Table 2, the remaining steps are the same as those of embodiment 1, and the detection indicators and methods are the same as those of embodiment 1.

[0097] Example 13

[0098] The difference between this embodiment and embodiment 1 is that the process parameters of this embodiment are as shown in Table 2, the remaining steps are the same as those of embodiment 1, and the detection indicators and methods are the same as those of embodiment 1.

[0099] Embodiment 14

[0100] The difference between this embodiment and embodiment 1 is that the distribution ratio of each group in the raw materials of this embodiment is as shown in Table 1, the remaining steps and parameters are the same as those of embodiment 1, and the detection indicators and methods are the same as those of embodiment 1.

[0101] Comparative Example 1

[0102] The difference between this comparative example and Example 1 is that the proportion of each group in the raw materials of this comparative example is as shown in Table 3, and the sum of the contents of PbO and CdO in the batch material is 0.5% by mole percentage, which is significantly lower than the sum of the contents of PbO and CdO in the example. The remaining steps and parameters are the same as those in Example 1, and the detection indicators and methods are the same as those in Example 1.

[0103] Comparative Example 2

[0104] The difference between this comparative example and Example 1 is that the distribution ratio of each group in the raw materials of this comparative example is as shown in Table 3, and the components do not contain BaF2; the remaining steps and parameters are the same as those in Example 1, and the detection indicators and methods are the same as those in Example 1.

[0105] Comparative Example 3

[0106] The difference between this comparative example and Example 1 is that the distribution ratio of each component in the raw materials of this comparative example is as shown in Table 3, the molar percentage of SiO2 in the glass component is 75%, which is significantly lower than the content of SiO2 in the example; and no Al2O3 is added to the glass component; the remaining steps and parameters are the same as those in Example 1, and the detection indicators and methods are the same as those in Example 1.

[0107] Comparative Example 4

[0108] The difference between this comparative example and Example 1 is that the distribution ratio of each group in the raw materials of this comparative example is as shown in Table 3, and the sum of the contents of KFH2 and K2SiF6 is 5% by mole percentage, which is significantly higher than the sum of the contents of KFH2 and K2SiF6 in the example. The remaining steps and parameters are the same as those in Example 1, and the detection indicators and methods are the same as those in Example 1.

[0109] Comparative Example 5

[0110] The difference between this comparative example and Example 1 is that the distribution ratio of each group in the raw materials of this comparative example is as shown in Table 3, and the sum of the contents of K2O and Na2O is 1% by mole percentage, which is significantly lower than the sum of the contents of K2O and Na2O in the example. The remaining steps and parameters are the same as those in Example 1, and the detection indicators and methods are the same as those in Example 1.

[0111] Comparative Example 6

[0112] The difference between this comparative example and Example 1 is that its preparation process is shown in Table 4. During the preparation of glass, the melting temperature is 1700° C., which is significantly higher than the melting temperature of the example. The remaining steps and parameters are the same as those of Example 1, and the detection indicators and methods are the same as those of Example 1.

[0113] Comparative Example 7

[0114] The difference between this comparative example and Example 1 is that the preparation process is shown in Table 4, and during the precision annealing process of preparing the glass, the temperature is raised to 700° C. at a heating rate of 3.0° C. / min. The remaining steps and parameters are the same as those in Example 1, and the detection indicators and methods are the same as those in Example 1.

[0115] Comparative Example 8

[0116] The difference between this comparative example and Example 1 is that the preparation process is shown in Table 4, and the furnace is not preheated before the batch material is added to the furnace, and the batch material is directly added to the furnace and then heated. The remaining steps and parameters are the same as in Example 1, and the detection indicators and methods are the same as in Example 1.

[0117] In the following tables, Table 1 is the glass composition of each embodiment; Table 2 is the process conditions of each embodiment; Table 3 is the glass composition of each comparative example; Table 4 is the process conditions of each comparative example; Table 5 is the test results of the embodiments and the comparative examples.

[0118] Each component in Table 1 and Table 3 is a molar percentage, in %. Among them, K1 in Table 1 and Table 3 is the molar percentage of SiO2 and (KHF2 + K2SiF6); K2 is the molar percentage of (SiO2 + K2O + Na2O) and (B2O3 + Al2O3); K3 is the molar percentage of (SiO2 + Al2O3) and (PbO + CdO).

[0119] The supplementary explanation of Table 5 is as follows:

[0120] A represents the refractive index of glass;

[0121] B represents the softening temperature of glass T f , unit is ℃;

[0122] C represents the compressive strength of glass; unit: MPa

[0123] D represents the anti-crystallization performance of the glass;

[0124] E represents the transmittance of the glass before irradiation, in %, and is measured by an ultraviolet spectrophotometer at 560 nm;

[0125] F means the glass is irradiated with 100Gy of neutrons and its transmittance at 560nm is measured by UV spectrophotometer, the unit is %;

[0126] G represents the difference between E and F, that is, the difference in transmittance of glass after neutron irradiation with a dose of 100 Gy, in %.

[0127] H represents the thickness of the glass sample used in the neutron irradiation test, in mm. The test method is to obtain a double-sided polished glass sample with a thickness of 10 mm after optical processing.

[0128] Table 1 Ratio of raw material components in each embodiment

[0129]

[0130] Table 2 Preparation process conditions of each embodiment

[0131]

[0132] Table 3 Ratio of raw material components in each comparative example

[0133]

[0134]

[0135] Table 4 Preparation process conditions of each comparative example

[0136]

[0137] Table 5 Test results of various embodiments and comparative examples

[0138] Group A B C D E F G H Example 1 1.472 692 1520 excellent 91.8 90.7 1.1 10 Example 2 1.472 682 1620 excellent 91.5 90.3 1.2 10 Example 3 1.465 674 1670 excellent 92.1 91.3 0.8 10 Example 4 1.468 683 1590 excellent 92.1 90.9 1.2 10 Example 5 1.473 699 1760 excellent 91.9 90.7 1.2 10 Example 6 1.474 653 1575 excellent 92.3 91.3 1.0 10 Example 7 1.476 651 1610 excellent 93.1 92.1 1.0 10 Example 8 1.479 679 1630 excellent 92.8 91.6 1.2 10 Example 9 1.468 677 1680 excellent 91.6 90.7 0.9 10 Example 10 1.479 691 1590 good 91.4 90.1 1.3 10 Embodiment 11 1.475 669 1710 good 92.3 91.0 1.3 10 Example 12 1.477 683 1730 excellent 91.9 91.3 0.6 10 Example 13 1.466 692 1590 excellent 91.4 90.9 0.5 10 Embodiment 14 1.470 684 1640 excellent 92.3 91.6 0.7 10 Comparative Example 1 1.476 671 1550 excellent 92.2 75.3 16.9 10 Comparative Example 2 1.492 661 1480 excellent 91.5 90.2 1.3 10 Comparative Example 3 1.473 629 1670 good 91.2 90.6 0.6 10 Comparative Example 4 - - - Difference - - - - Comparative Example 5 1.465 738 1610 excellent 92.2 91.3 0.9 10 Comparative Example 6 1.508 702 1570 excellent 92.8 91.8 1.0 10 Comparative Example 7 - - - - - - - - Comparative Example 8 - - - - - - - -

[0139] In conjunction with the embodiments, the data in Tables 1, 2, and 5 and the attached Figure 1 It can be seen that the glass n prepared by the present invention for liquid scintillation capillary array d 1.465~1.480; softening temperature T f Between 650 and 700℃; no crystallization and phase separation at 750-1100℃, with good anti-crystallization performance and glass stability; glass compressive strength ≥1500Mpa; glass used for liquid scintillator capillary array when the thickness is 10mm, use 252 Cf is used as a fast neutron radiation source. After being irradiated with a total dose of 100 Gy of fast neutrons, the transmittance at 560 nm decreases by ≤1.3%, which shows excellent radiation resistance. It can be seen that the glass prepared in this embodiment has excellent properties in many aspects, can be used to prepare liquid scintillator capillary arrays, and is further applied to fast neutron imaging detectors, and has a wide range of promotion and application prospects in the field of neutron detection.

[0140] Further analysis of the embodiments shows that when the sum of the contents of Na2O and K2O is limited to 2-5%, the refractive index of the prepared glass is lower; when the sum of the contents of KFH2 and K2SiF6 is 2-4%, and the contents of KHF2 and K2SiF6 are in the range of 20-60:1, the ratio of the total content of SiO2, K2O and Na2O to the total content of B2O3 and Al2O3 is in the range of 10-14:1, and the ratio of the total content of SiO2 and Al2O3 to the total content of PbO and CdO is in the range of 40-90:1, the prepared glass has a lower refractive index, better anti-crystallization performance, and excellent glass transmittance and radiation resistance.

[0141] Furthermore, in Comparative Example 1, the sum of the contents of PbO and CdO is less than 1%, only 0.5%, resulting in poor radiation resistance. After 100 Gy neutron irradiation, the transmittance is reduced by 16.9%, which is difficult to meet the use requirements.

[0142] Furthermore, in Comparative Example 2, BaF2 is not added, resulting in the glass refractive index of the component exceeding 1.48%, which is difficult to meet the use requirements.

[0143] Furthermore, in Comparative Example 3, the molar percentages of SiO2 and Al2O3 are significantly lower than those in the embodiment. From the test results, it can be seen that the softening point is significantly reduced, resulting in severe deformation during the hot melt pressing process of capillary array preparation, resulting in reduced detection efficiency. At the same time, due to the reduced proportion of skeleton structure components, the anti-crystallization performance is deteriorated, resulting in different degrees of crystallization during hot melt pressing processes such as wire drawing.

[0144] Furthermore, in Comparative Example 4, the sum of the contents of KFH2 and K2SiF6 is significantly higher than the maximum value of the sum of the contents of KFH2 and K2SiF6 strictly limited by the present invention, resulting in a significant increase in the crystallization tendency of the glass, making it difficult to prepare the corresponding glass tube. The reason is that excessive fluoride doping causes the glass to become opacified. This is because the solubility of fluoride in the glass melt is limited, and excess fluoride will precipitate in the form of tiny crystalline particles, thereby reducing the glass-forming properties and increasing the crystallization tendency.

[0145] Furthermore, in Comparative Example 5, the sum of the contents of K2O and Na2O is 1%, which is significantly lower than the minimum value of the sum of the contents of K2O and Na2O strictly limited by the present invention, resulting in an increase in the difficulty of melting the glass and a significant increase in the softening temperature, which further makes it difficult for the glass tube to match the light absorbing material, causing obstacles to the subsequent wire drawing process; the reason is that potassium and sodium are typical alkali metals, which exist in the form of ions in the glass. When potassium and sodium ions are doped in the glass, they will enter the silicon oxygen network structure of the glass. These alkali metal ions have a large radius and a small number of charges. They play the role of "network breakers" in the glass structure, making the silicon oxygen network structure loose. When the glass is heated, this loose structure makes it easier for the ions to move, and the glass is easier to soften; when the doping amount of potassium and sodium is reduced, the silicon oxygen network structure of the glass is relatively complete and tight, and it is more difficult for the ions to move and rearrange, so a higher temperature is required to soften the glass, that is, the softening temperature of the glass increases. The increase in the softening temperature of the glass further increases the viscosity difference between the glass and the light-absorbing wire, leading to problems such as difficulty in matching the glass and the light-absorbing wire and difficulty in the subsequent wire drawing process.

[0146] Furthermore, in Comparative Example 6, the melting temperature is higher than the maximum value of the melting temperature limit of the present invention, resulting in excessive volatilization of volatile components in the glass components, and the refractive index of the molten glass becomes higher. The reason is that: the boiling point of fluoride is low, and the excessively high melting temperature causes excessive volatilization of fluoride components. Since fluoride can significantly reduce the refractive index, it will cause the refractive index to increase, making it difficult to meet the design and use requirements of the glass.

[0147] Furthermore, in Comparative Example 7, during the precision annealing process, the heating rate was too fast and the holding temperature was too high, resulting in deformation of the glass during annealing; the reason is that when the annealing temperature is higher than the softening temperature of the glass, the glass will deform due to its own gravity. Because above the softening temperature, the viscosity of the glass is significantly reduced, the particles inside the glass can move more easily, and the glass cannot maintain its original shape at this time. At the same time, too high a temperature may also cause greater thermal stress inside the glass. This is because the temperature changes in different parts of the glass are uneven and the degree of thermal expansion is different. This thermal stress may cause cracks or even breakage in the glass.

[0148] Furthermore, in Comparative Example 8, during the preparation process, the batch materials were not preheated before being added to the furnace, resulting in poor uniformity of the glass, reduced strength, and easy cracking. The reason is that: at the initial stage of heating, the batch materials close to the crucible wall are heated faster, while the internal batch materials are heated slowly, which will cause uneven heating of the batch materials. This may cause local differences in the composition of the glass liquid, resulting in different melting and reaction progress of raw materials at different locations, affecting the quality uniformity of the glass. Secondly, this uneven heating may produce a large temperature gradient in the glass liquid, thereby inducing thermal stress. The generation of thermal stress can easily cause cracks in the glass and reduce the product qualification rate.

[0149] The technical features in the claims and / or the specification of the present invention may be combined, and the combination is not limited to the combination obtained by reference in the claims. The technical solution obtained by combining the technical features in the claims and / or the specification is also within the protection scope of the present invention.

[0150] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A glass for liquid scintillation capillary array, characterized in that: The glass components are expressed in mole percentages and include: 80-85% SiO2; 0.5-4% Al2O3; 4.5-8% B2O3; the sum of K2O and Na2O is 2-8%; the sum of PbO and CdO is 1-2%; 1.5-4% ZrO2; the sum of KFH2 and K2SiF6 is 1-4%; 0.2-0.5% BaF2; 0.5-1% CeO2.

2. The glass according to claim 1, characterized in that The sum of the K2O and Na2O contents is 2-5%.

3. The glass according to claim 1, characterized in that The ZrO2 is 2-4%.

4. The glass according to claim 1, characterized in that The sum of the contents of KFH2 and K2SiF6 is 1.5-4%.

5. The glass according to claim 1, characterized in that The following conditions are met: a. The molar percentage of SiO2 is X1, the total molar percentage of KHF2 and K2SiF6 is X2, and X1: X2 is 20 to 75: 1; b. The total molar percentage of SiO2, K2O and Na2O is X3, and the total molar percentage of B2O3 and Al2O3 is X4; X3:X4 is 9-14:1; c. The total molar percentage of SiO2 and Al2O3 is X5, the total molar percentage of PbO and CdO is X6, and X5:X6 is 40 to 90:

1.

6. The glass according to claim 5, characterized in that One or more of the following conditions are met: a. the ratio of X1:X2 is 20 to 60:1; b. the ratio of X3:X4 is 10 to 14:1; c. the ratio of X5:X6 is 50 to 90:

1.

7. The glass according to any one of claims 1 to 6, characterized in that: The glass refractive index n d 1.465~1.480; no crystallization at 750~1100℃; softening temperature T f 650~700℃; the compressive strength of the glass is ≥1500Mpa; when the thickness is 10mm, use 252 When Cf is used as a fast neutron radiation source, after being irradiated with a total dose of 100 Gy of fast neutrons, the transmittance at 560 nm decreases by ≤1.3%.

8. A method for preparing glass for liquid scintillation capillary array, characterized in that: It includes the following steps: S1: The raw materials are uniformly mixed to prepare a batch material; in terms of molar percentage, the batch material includes 80-85% SiO2; 0.5-4% Al2O3; 4.5-8% B2O3; the sum of K2O and Na2O is 2-8%; the sum of PbO and CdO is 1-2%; 1.5-4% ZrO2; the sum of KFH2 and K2SiF6 is 1-4%; 0.2-0.5% BaF2; and 0.5-1% CeO2; S2: Melting, clarifying and homogenizing the batch material prepared in S1 to obtain glass liquid; S3: After cooling the glass liquid obtained in S2 to 1200-1300°C, it is molded and precision annealed in sequence.

9. The preparation method according to claim 8, characterized in that: The S2 melting temperature is 1500-1600°C and the melting time is 10-15h.

10. The preparation method according to claim 8, characterized in that: The method further comprises the following steps: before the batch material is melted, a melting device for melting the batch material is preheated to a temperature of 1300-1400°C.

11. The preparation method according to any one of claims 8 to 10, characterized in that: The precision annealing comprises: heating to 550-650° C. at 1.5-2.5° C. / min, maintaining the temperature for 5-8 hours, and then cooling to room temperature at 1.0-2.0° C. / h.

12. A liquid scintillator micropore array detector, characterized in that: The glass capillaries in the micropore array area are made of the glass described in any one of claims 1 to 7; and the liquid scintillator is filled in each microcapillary of the capillary array.

Citation Information

Patent Citations

  • Capillary tube array and preparation method and application thereof

    CN117214994A

  • High-resolution microstructure cold and hot neutron imaging scintillation screen and preparation method thereof

    CN118151212A

  • Optical glass having a small photoelastic constant

    CN1597583A

  • Glass ceramic and method for producing the same

    JP2011093764A

Cited By

  • Light absorption glass for preparing liquid flash capillary tube array and preparation method and application of light absorption glass

    CN122167031A